2013
DOI: 10.1002/oby.20083
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol, obesity, and the metabolic syndrome: A cross‐sectional study of obese subjects and review of the literature

Abstract: Circulating cortisol and psychosocial stress may contribute to the pathogenesis of obesity and metabolic syndrome. To evaluate these relationships, we performed a cross-sectional study of 369 overweight and obese subjects and 60 healthy volunteers and reviewed the previous literature. Overweight and obese subjects had at least two other features of Cushing’s syndrome. They underwent measurements representing cortisol dynamics (24h urine cortisol excretion (UFC), bedtime salivary cortisol, 1 mg dexamethasone su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
131
5
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(151 citation statements)
references
References 41 publications
9
131
5
6
Order By: Relevance
“…Despite these findings however, another study found that after 1.0 mg of dexamethasone, cortisol concentrations in serum were not associated with BMI (Abraham et al, 2013), and similarly, a sample of females found no relationship with any obesity measure and inhibition of cortisol secretion after 1.0 mg dexamethasone administration (Mårin et al, 1992). This study, however, did not measure or account for abdominal measures of obesity.…”
Section: Glucocorticoid Feedback Sensitivity -Dexamethasone Suppressicontrasting
confidence: 65%
See 3 more Smart Citations
“…Despite these findings however, another study found that after 1.0 mg of dexamethasone, cortisol concentrations in serum were not associated with BMI (Abraham et al, 2013), and similarly, a sample of females found no relationship with any obesity measure and inhibition of cortisol secretion after 1.0 mg dexamethasone administration (Mårin et al, 1992). This study, however, did not measure or account for abdominal measures of obesity.…”
Section: Glucocorticoid Feedback Sensitivity -Dexamethasone Suppressicontrasting
confidence: 65%
“…Given the strong pattern of findings and the fact that some of the literature has attempted to examine generalized and abdominal obesity independently, the GRADE rating of the the strength of this evidence would be "moderate-to-high." This consistent pattern of findings is of marked importance in this population as obese individuals tend to experience more repeated stressors (Abraham et al, 2013;Nyberg et al, 2012). In light of this evidence, high prevalence of life stressors paired with an overactive cortisol response may in fact perpetuate obesity and HPA-related diseases.…”
Section: Cortisol Reactivitymentioning
confidence: 53%
See 2 more Smart Citations
“…Similarly, night‐time urine cortisol was higher in obese human patients than in normal weight controls 13. Although a hypothetical role of glucocorticoids in human obesity has been suggested,13 the role is debated with inconclusive results regarding the assumed positive relationship between cortisol secretion and body fat content 39. Increased sensitivity along the hypothalamic‐pituitary‐adrenal axis as well as peripheral alterations of cortisol metabolism could play a role in the pathophysiology of abdominal obesity 13.…”
Section: Discussionmentioning
confidence: 99%